Youtube as an Alternative for Distance Learning (DL) Chemistry: Study of Interests and Motivation - Sri Rahmania; Rabiah Afifah Daulany (Journal of Educational Chemistry (JEC), 2021)
This study aims to determine the interests and motivations of students in learning chemistry by utilizing YouTube as an alternative platform in distance learning. This type of research is descriptive quantitative research. Data were obtained from the survey of interest and motivation questionnaires using google forms taken for five weeks during the learning process. The respondents of this study were 100 students majoring in chemistry who studied organic chemistry using YouTube as a distance learning platform. The results showed that youtube as an alternative platform for distance learning (DL) is considered very good for positively impacting students' interest and motivation in studying chemistry. But in its use, it must be accompanied by applications or other media that can support the learning process, especially on material related to the experiment. In addition, in using YouTube, it is necessary to pay attention to aspects such as sound quality, image quality, size of writing, and clarity of the material so that the material presented is easy to understand, straightforward and exciting.